SISTEM INFORMASI KEPENDUDUKAN PADA KANTOR LURAH KELURAHAN TOBOLOLO BERBASIS WEBSITE - nurlya udrus (JAMINFOKOM - Jurnal Manajemen Informatika dan Komputer, 2023)
Information System Is Intended to Increase Efficiency In Terms Of Public Services. Kelurahan Tobololo West Ternate City So Far Have an Information Systen thet is still in manual form so that it makes it difficudl and slows down the procces of adding, deleteting, and changingbin making letters.Therefore it is necessary to do researccto design an information system website community. The purpose of this information system is to provide cobvenience to the community in managing document kelurahan, the steps taken in this case are system requirements analysis, system design, and implementation, using the php programming language and the database using Mysql